(untitled) (Journal of Media studies, 2021)
The aim of the article is to analyze the internal environmentand offer solutions to identified problems of one of the domestic companies thatfunctions in the diary sector of our economy in the Republic of Kazakhstan. Theobjectives of the study are: to conduct the literature review and carry out theorganizational analysis by means of diagrams like “SIPOC”, “Affinity diagram”and the “Interrelationship diagram” which in turn help to analyze the wholecompany (AMIL LLP). The Force Field Analysis Model of Kurt Lewin has beentaken as a theoretical basis of the study. This model gives an understanding ofindividual and group behavior as determined by motivation and expectation. Theliterature review was conducted in order to clarify the concepts of changemanagement. The theoretical contribution is in the fact that some attempts havebeen done to determine the importance of change management activities inproduction companies like AMIL LLP.